“MULHER É TUDO NA CASA”: MULHERES E MEMÓRIAS NO FAXINAL BARRA BONITA - Petriw, Claudete Maria (2019)
The aim of this dissertation is to analyze, in an incessant way, the gender relations, self-construction and the construction of place present in the (re)built memory of women and men from the Faxinal Barra Bonita. Our focus is to understand how women see, understand, report and reflect on themselves and on their relationships with men and with place. In order to do so, we made use of the theoretical-methodological contribution of oral history. The sources used for the analysis in this research are interviews carried out with 21 (twenty-one) people, from March 2018 to January 2019, 17 (seventeen) of whom currently live in the Faxinal Barra Bonita. Other 4 (four) interviews were carried out with women who lived in the faxinal and migrated to another locality. We considered the conceptual notion of place under Michel de Certau’s view (1988), as a practiced space, and that such space can be constantly built from its recollections. The specific aims of this research are geared to the debate of gender relations and women’s place(s), so as to understand how the conditions and the ways of life of the women from the Faxinal Barra Bonita are produced, as well as how the community gets organized in relation to its knowledge and daily chores using a system of significations assigned to male and to female; it also analyzes, from the social point of view, the exodus of women to urban centers. At first, we tried to historicize the formation of the Faxinal Barra Bonita, permeating the academic knowledge with the elderly dwellers’ recollections, analyzing how gender links with memory to think and build the faxinal history. Next, we seek to analyze the daily gender relations in the Faxinal Barra Bonita from the memories regarding our interviewees’ childhood and youth, in order to understand how these people build their subjectivity and organize the chores, the practices and the cultural values from gender relations. Finally, we analyze the lives of women, mothers and wives, as well as people’s perceptions on the changes in the social and economic dynamics of the faxinal, and on the possibilities of life outside it, as a reflection that they make on their own aging.